2006
DOI: 10.1097/01.gim.0000232582.91028.03
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the definition of a positive family history for early-onset coronary heart disease

Abstract: Purpose: Assessing familial risk for early-onset coronary heart disease (CHD) is typically limited to first-degree relatives with early-onset CHD. To evaluate the impact of additional family history, we examined the associations between various family history definitions and early-onset CHD. Methods: By using the national HealthStyles 2003 survey data, we assessed associations between self-reported family history and personal history of early-onset CHD (diagnosed at or before age 60 years), adjusting for demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…Algorithms for stratifying risk that incorporate these features of family history to rank individual people are being evaluated in adult populations. [91][92][93] Algorithms to predict the risk of chronic conditions in susceptible children may have to be modified to account for the potentially prolonged period between exposure and outcomes. Ideally, the algorithm should identify children at increased risk who would benefit the most from early preventive measures and children at very high risk, who may be referred to a specialist.…”
Section: Family History As a Screening Toolmentioning
confidence: 99%
“…Algorithms for stratifying risk that incorporate these features of family history to rank individual people are being evaluated in adult populations. [91][92][93] Algorithms to predict the risk of chronic conditions in susceptible children may have to be modified to account for the potentially prolonged period between exposure and outcomes. Ideally, the algorithm should identify children at increased risk who would benefit the most from early preventive measures and children at very high risk, who may be referred to a specialist.…”
Section: Family History As a Screening Toolmentioning
confidence: 99%
“…43 Once thought to be relevant only if parental disease was "early" (the definition of which has varied in numerous studies, typically being age 55 or younger in men and age 60 in women), risk is now associated with coronary heart disease of any age of onset in any first-or second-degree relative. 44 In addition, family history is relevant for subclinical disease, such as coronary artery calcification 45,46 and the risk of sudden death during an acute coronary event. 47 As with type 2 diabetes, GWAS has uncovered dozens of loci that are associated with increased risk of coronary artery disease.…”
mentioning
confidence: 99%
“…1,[5][6][7]9,[11][12][13] Studies that have investigated family histories of late-onset CHD have also found significant positive associations with CHD, although the relative risks are comparatively smaller. 5,6,9,[11][12][13] Recent studies have demonstrated an increased CHD risk associated with CHD in second-degree relatives, 14,15 and in maternal relatives, 13 although other studies have not found an association between CHD and lineage. 4,7,10,16 Despite the importance of family history as a CHD risk factor, it is underused in CHD prevention efforts.…”
mentioning
confidence: 99%